2015
DOI: 10.1080/09593330.2015.1012181
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-bed adsorption of toluene on high silica zeolites: experiments and mathematical modelling using LDF approximation and a multisite model

Abstract: The adsorption of toluene (TOL) as a target volatile organic compound has been studied experimentally and modelled on various hydrophobic zeolites: Faujasite (FAU), ZSM-5 (Z) and Mordenite (MOR). The influence of the nature of the compensating cation (H+ or Na+) has also been investigated for ZSM-5 zeolite, which is known to possess three kinds of adsorption sites (sinusoidal channels, straight channels and intersections). Type I isotherms observed on FAU, Na-Z and MOR fitted well with the Langmuir model. A de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…IR evidence obtained here suggests that a surface reaction occurs between adsorbed toluene at Brønsted acid sites and active oxygen species generated after ozone adsorption and decomposition at Lewis acid sites. Such a surface reaction mechanism is in agreement with previous reports, that claim the adsorption of toluene molecules at Brønsted acid sites and the adsorption of ozone molecules at Lewis acid sites followed by its transformation into active oxygen species [32,48,[55][56][57]. After that, it has been indicated that active oxygen species interact with adsorbed toluene molecules, leading to the formation of toluene oxidation by-products, as reported elsewhere [58,59].…”
Section: Ftir Evidence Of the Heterogeneous Catalytic Ozonation Of To...supporting
confidence: 92%
See 1 more Smart Citation
“…IR evidence obtained here suggests that a surface reaction occurs between adsorbed toluene at Brønsted acid sites and active oxygen species generated after ozone adsorption and decomposition at Lewis acid sites. Such a surface reaction mechanism is in agreement with previous reports, that claim the adsorption of toluene molecules at Brønsted acid sites and the adsorption of ozone molecules at Lewis acid sites followed by its transformation into active oxygen species [32,48,[55][56][57]. After that, it has been indicated that active oxygen species interact with adsorbed toluene molecules, leading to the formation of toluene oxidation by-products, as reported elsewhere [58,59].…”
Section: Ftir Evidence Of the Heterogeneous Catalytic Ozonation Of To...supporting
confidence: 92%
“…After that, it has been indicated that active oxygen species interact with adsorbed toluene molecules, leading to the formation of toluene oxidation by-products, as reported elsewhere [58,59]. Previously published works confirm the surface reaction mechanism proposed here, using not only natural zeolite mainly composed of clinoptilolite and mordenite and modified natural zeolite [32,48]; but also using synthetic zeolites such as faujasite, mordenite, and ZSM-5 [55][56][57] under the same experimental conditions.…”
Section: Ftir Evidence Of the Heterogeneous Catalytic Ozonation Of To...supporting
confidence: 86%
“…Bulky VOCs, whose size exceeds the zeolite pore dimensions hinders effective adsorption. Nicolas et al [25] investigated toluene adsorption as a function of zeolite channel size and pore structure using three commercial hydrophobic zeolites: mordenite (MOR), ZSM-5, and faujasite (FAU) zeolite. They evidenced that toluene could be readily absorbed by FAU zeolite, however, decreased adsorption capacities were observed when using MOR and ZSM-5, suggesting the importance of the zeolite structures.…”
Section: Adsorption Of Vocs Over Zeolitesmentioning
confidence: 99%
“…There are a wide range of VOC treatment technologies for aromatics, mainly adsorption (activated carbon, zeolite, resin, , and metal–organic framework ), catalytic oxidation, and absorption . Among these methods, absorption is highly preferred because of the advantages of simple equipment, easy operation, and wide applicability.…”
Section: Introductionmentioning
confidence: 99%